2003
DOI: 10.1038/sj.onc.1206832
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of LAPTM4B, a novel gene upregulated in hepatocellular carcinoma

Abstract: Lysosomal-associated protein transmembrane-4 beta (LAPTM4B), a novel gene upregulated in hepatocellular carcinoma (HCC), was cloned using fluorescence differential display, RACE, and RT-PCR. It contains seven exons and encodes a 35-kDa protein with four putative transmembrane regions. Both the N-and C-termini of the protein are proline-rich, and may serve as potential ligands for the SH3 domain. Immunohistochemical analysis localized the protein predominantly to intracellular membranes. Northern blot showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 43 publications
5
163
0
1
Order By: Relevance
“…They found that despite high cytotoxic activity of CIK against lymphoma cells, they had little toxicity against a subset of normal human hematopoietic progenitor cells. Some difference between Bel-7402 and L-02 has been reported recently by Shao et al [26] , that LAPTM4B, a newly found HCC related antigen, was expressed in Bel-7402 but not in L-02. A polyclonal antibody against LAPTM4b has been produced.…”
Section: Discussionmentioning
confidence: 98%
“…They found that despite high cytotoxic activity of CIK against lymphoma cells, they had little toxicity against a subset of normal human hematopoietic progenitor cells. Some difference between Bel-7402 and L-02 has been reported recently by Shao et al [26] , that LAPTM4B, a newly found HCC related antigen, was expressed in Bel-7402 but not in L-02. A polyclonal antibody against LAPTM4b has been produced.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies indicate that LAPTM4B plays an important role in tumourigenesis (13,14,19), although its exact mechanism of action remains to be elucidated. The over-expression in ACTH-secreting tumours demonstrated by the microarray analysis and confirmed with the RQ-PCR analysis of grouped tumours may relate to the abundant lysosomes present in corticotroph adenomas (20).…”
Section: Rq-pcrmentioning
confidence: 99%
“…LAPTM4B is a member of the mammalian LAPTM family that comprises LAPTM4A, LAPTM4B and LAPTM5 (Adra et al, 1996;Hogue et al, 2002;Shao et al, 2003). All LAPTM family members are small multitransmembrane proteins that, when overexpressed, are targeted to the late endosome and/or lysosome (Hogue et al, 2002;Milkereit and Rotin, 2011;Pak et al, 2006;Shao et al, 2003;Vergarajauregui et al, 2011); however, endogenous LAPTM4B is localized to both early and late endosomes (Tan et al, 2015a). LAPTM4B is an oncoprotein that is overexpressed in numerous human cancers of undefined oncogenic mechanisms (Kasper et al, 2005).…”
Section: Intracellular Ptdins(45)p 2 Signalingmentioning
confidence: 99%